2021
DOI: 10.3390/met11071062
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Plants and Biomass Wastes as Organic Green Corrosion Inhibitors for Mild Steel in Acidic Environment

Abstract: Acid corrosion is a problem pertaining to corrosion that involves an acid solution. It is important to treat metal to preserve its integrity. Thus, acids are utilized to clean and treat metal surfaces. In return, this may lead to over-etching and metal degradation. Corrosion inhibitors were introduced as a solution for the issue. However, there are some problems associated with the usage of conventional corrosion inhibitors. Traces of nitrites and chromates that are present in the inhibitors may lead to seriou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…Therefore, the IE is increased and CR is also reduced, when the concentration of combined inhibitor (AO-Zn 2+ ) system is increased (30,40) . https://www.indjst.org/ Anodic reaction (28,41) : Fe → Fe 2+ + 2e − Cathodic reaction (41) :…”
Section: Weight-loss Methods For Ao-zn 2+ Systemmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the IE is increased and CR is also reduced, when the concentration of combined inhibitor (AO-Zn 2+ ) system is increased (30,40) . https://www.indjst.org/ Anodic reaction (28,41) : Fe → Fe 2+ + 2e − Cathodic reaction (41) :…”
Section: Weight-loss Methods For Ao-zn 2+ Systemmentioning
confidence: 99%
“…CS was immersed in well water with various concentrations of AO leaves at 303K. After one day of immersion, CS samples were collected, washed with tap water, dried and gauged to determine the IE (27,28) and CR (28)(29)(30) using the following equations:…”
Section: Determination Of Ie and Crmentioning
confidence: 99%
See 2 more Smart Citations
“…A study by Kadhum et al [22] in 2021 revealed that considerable improvements in corrosion resistance of up to 80% were observed when using organic compounds as corrosion inhibitors. Recent review studies by Reza et al [23] and Yang [24] also discussed various types of organic corrosion inhibitors for mild steel application, which show excellent performance up to 90% in the acidic environment. Other beneficial properties of organic compounds include high inhibition effectiveness, cost-effectivity, ease of application and synthesis, and being more environmentally friendly than inorganic compounds [25,26].…”
Section: Organic Corrosion Inhibitorsmentioning
confidence: 99%